Mindfulness and Anxiety in Adolescents: Systematic Literature Review Based on Big Data - Jannah, Dwi Susi Miftakhul; Setiyowati, Ninik (Kuras Institute, 2024)
Adolescents are a group of individuals who are vulnerable to experiencing anxiety due to various factors that influence them. Anxiety that occurs in adolescents has several negative impacts on physique, psychology, and self-development of adolescents. If this anxiety is not overcome, it will evoke other symptoms and disorders that are more serious. Because of many negative impacts that arise when adolescents experience anxiety, an intervention is needed to overcome it, one of which can be done with mindfulness. This research uses a systematic literature review method using Publish or Perish software to collect articles from several sources such as Google Scholar, Research Gate, SINTA, DOAJ and Scopus. The keywords used are “mindfulness”, “anxiety”, “kecemasan”, “remaja”, “adolescents” and “teenage”. Based on these keywords, more than 500 articles published in 2019-2024 were found. Next, the researcher used 16 articles that were closely related to this research with a total of samples of 6.034. The research results show that mindfulness has proven effective in overcoming adolescents’ anxiety and there is a negative relationship between mindfulness and anxiety that adolescents who have high mindfulness will have low anxiety and vice versa. There are several programs of mindfulness intervention that can be carried out by adolescents, ranging from formal to informal practices that can be practiced when doing daily activities according to needs, situations and conditions.